Success Factor Analysis of Multiple Project Management - Taftazani Hakim; Ervina Ahyudanari; Rita Ambarwati (IPTEK Journal of Proceedings Series, 2020)
PT XYZ is one of the largest manufacturing industry companies in Indonesia, that using multiple project management. Several concurrent projects existed, or also referred as multiple project management. Multiple project often cause several problems, such as the long duration of the project because of wrong determining priorities and limited resources. These problems certainly affect the success of the project in general. The success of the project is measured by the project iron triangle, that is budget, quality and time. Success of a project is important, and many research has been done to determine the project success factors. However, there is still limited research related to multiple projects. This is exploratory research, and initial stage where researchers will determine the factors that support the success of multiple projects. Following the variable identification from literature study, a survey was conducted. This research use exploratory factor analysis (EFA) and mean vs standard deviation analysis. Results of the study, success factors of multiple projects formed six factors including communication, organizational, technical, external, resource, and project factors. As a recommendation for the company, which factors are significant are seen from the results of the mean analysis, with the highest significance results are : (1) Material availability; (2) Realistic planning; and (3) Manager's competence